Dramatically increased rate of observed hot record breaking in recent Australian temperatures. Issue 18 (22nd September 2015) - Lewis, Sophie C.; King, Andrew D.
Abstract Persistent extreme temperatures were observed in Australia during 2012–2014. We examine changes in the rate of hot and cold record breaking over the observational record for Australia‐ and State‐wide temperatures. The number of new hot (high‐maximum and high‐minimum temperatures) temperature records increases dramatically in recent decades, while the number of cold records decreases. In a stationary climate, cold and hot records are expected to occur in equal frequency on longer than interannual time scales; however, during 2000–2014, new hot records outnumber new cold records by 12 to one on average. Coupled Model Intercomparison Project phase 5 experiments reveal increased hot temperature record breaking occurs in simulations that impose anthropogenic forcings but not in natural forcings‐only experiments. This disproportionate hot to cold record breaking rates provides a useful indicator of nonstationarity in temperatures, which is related to the underlying mean observed Australian warming trend of 0.9°C since high‐quality records began in 1910.